Are Indian Firms too Small? A Nonparametric Analysis of Cost Efficiency and the Optimal Organization of the Indian Manufacturing Industry. - Subhash C. Ray (Indian Economic Review, 2009)
In this paper we use the 2004-05 Annual Survey of Industries data to estimate the levels of cost efficiency of Indian manufacturing in the various states and also get state level measures of industrial organization (IO) efficiency. The empirical results show the presence of considerable cost inefficiency in a majority of the states. Further, we also find that, on average, Indian firms are too small. Consolidating them to attain the optimal scale would further enhance efficiency and lower average cost.